2019
DOI: 10.3389/fneur.2019.00809
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Network Disorganizations in Typical Epilepsy With Centro-Temporal Spikes and Impact on Cognitive Neurodevelopment

Abstract: Epilepsy with Centrotemporal Spikes (ECTS) is the most common form of self-limited focal epilepsy. The pathophysiological mechanisms by which ECTS induces neuropsychological impairment in 15–30% of affected children remain unclear. The objective of this study is to review the current state of knowledge concerning the brain structural and functional changes that may be involved in cognitive dysfunctions in ECTS. Structural brain imaging suggests the presence of subtle neurodevelopmental changes over the epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 170 publications
(226 reference statements)
1
9
0
1
Order By: Relevance
“…28 Otherwise, epileptogenic process may also be associated with delaying the normal cortical maturation process. 29 The consideration above agrees with our findings regarding the influence of the age of onset of crises over the interval between the first and last seizure, since the younger the child at the first seizure, the longer this interval will be, so that for each month of increase in the age of the child at the first seizure occurrence, the interval is reduced by 0.43 months. Likewise, age also had a strong impact on EEG normalization.…”
Section: Discussionsupporting
confidence: 90%
“…28 Otherwise, epileptogenic process may also be associated with delaying the normal cortical maturation process. 29 The consideration above agrees with our findings regarding the influence of the age of onset of crises over the interval between the first and last seizure, since the younger the child at the first seizure, the longer this interval will be, so that for each month of increase in the age of the child at the first seizure occurrence, the interval is reduced by 0.43 months. Likewise, age also had a strong impact on EEG normalization.…”
Section: Discussionsupporting
confidence: 90%
“…To date, numerous studies have demonstrated that the restingstate brain activity of children with CECTS has been altered (McGinnity et al, 2017;Bourel-Ponchel et al, 2019;Zhang et al, 2020). On this basis, several studies based on functional magnetic resonance (fMRI) have further investigated brain alterations in CECTS during AEDs treatment, the results of which have shown that AEDs have an effect on functional connectivity (FC) (Jiang et al, 2019(Jiang et al, , 2020), and regional activity (Zhang et al, 2017(Zhang et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…ECTS is often associated with neuropsychological deficits believed to reflect the interference between the epileptic focus and other brain regions during development. The cognitive dysfunctions observed in children with ECTS, including altered WM, have been linked to an abnormal developmental trajectory of brain structures, particularly those affected by epilepsy ( Besseling et al, 2013a , Bourel-Ponchel et al, 2019 , Ciumas et al, 2014 , Garcia-Ramos et al, 2015 , Garcia-Ramos et al, 2016 , Hutchinson et al, 2010 , Lin et al, 2012 , Tosun et al, 2011 , Widjaja et al, 2013 ). Task-based functional neuroimaging studies have shown that ECTS is associated with: 1) reduced activity during verbal generation task within language-related regions, in particular over the anterior language network ( Lillywhite et al, 2009 ), 2) a wider network recruitment during sentence reading comprehension ( Malfait et al, 2015 ), 3) reduced language laterality index, with more bilateral and right-hemispheric activations ( Datta et al, 2013 ) , 4) remodelling of language networks ( Vannest et al, 2013 ) and 5) altered responses to fearful stimuli ( Ciumas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%